Bruce Bronzan for State Assembly Fundraiser at The Star Palace - Watkins, Howard::::::::: (1979)
Guests dancing in the streets due to fire inside Star Palace: John Donaldson, Shirley Donaldson, ?,?, ?Lois Lyness